Use of cauda epididymis extract as immunocontraceptive - Risvanli, A; Aydin, M; Kaygusuzoglu, E; Bulut, H; Apaydin, AM; Timurkan, H (Elsevier Science Inc, 2002)
The objective of this study was to evaluate use of a cauda epididymis extract (CEE) as an immunocontraceptive in rats. Twenty-two rats in puberty or 19 rats that gave birth once (primipara) were immunized with intraperitoneal (IP) injection of CEE. Rats in puberty received one or two injections of CEE containing 1.5 X 10(9) sperm/mL, while primipara rats received injections of CEE containing 3 X 10(6) sperm/mL up to three times. Animals were tested for the presence and concentration of anti-CEE antibody by enzyme-linked immunosorbent assay (ELISA) and monitored for pregnancy following natural insemination. Results revealed that 38 (92.6%) of the 41 rats were positive for anti-CEE antibodies, regardless of animal type or immunization procedure. However, there was no relation between pregnancy rates and concentration of anti-CEE antibody in rats immunized with CEE. These results indicate that immune response against CEE may not play a major role in contraception in rats. (C) 2002 Elsevier Science Inc. All rights reserved.
Keywords: immunocontraception; cauda epididymis extract; rat